Diaphragmatic speckle tracking imaging for 2D-strain assessment in mechanical ventilation weaning test. (July 2021) - Crognier, Laure; Poette, Mickael; Conil, Jean-Marie; Lairez, Olivier; Minville, Vincent
Abstract: Ultrasound (US) is recognized as a useful tool for detecting lung physiology and pathology. Lung US is compared with standard techniques for evaluating lung structure and function such as computed tomography and pulmonary function tests. At present, markers of normal physiology and pathology are detected using expected image patterns. Detecting the latter depends on the experience of the operator. Diaphragmatic dysfunction is a particularly frequent problem in intensive care. Diaphragmatic dysfunction is easily assessed using lung US. Speckle tracking analysis, a known method for assessing tissue displacement and deformation in cardiology, is proposed to be utilized in lung US for detecting and quantifying lung sliding. Using speckle tracking analysis to diaphragmatic deformation quantification could be an informative and new tool for weaning from mechanical ventilation.